2020
DOI: 10.4314/ejhs.v30i3.15
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Rate of Diabetes and Hypertension in Disaster-Exposed Populations: A Systematic Review and Meta-Analysis

Abstract: BACKGROUND: Non-communicable diseases (NCD) such as hypertension (HTN) and diabetes mellitus (DM) have been one of the major health problems in the world. The aim of this study was to evaluate the prevalence rate of DM and HTN following natural and man-made disasters that impose significant economic and psychological burdens on human communities.METHODS: In this systematic and meta-analysis review, all crosssectional studies that at least one of their objectives was to measure the prevalence of HTN or DM in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 55 publications
2
11
1
Order By: Relevance
“…Elevated BP due to the pandemic is in line with prior research on social disruption following natural disasters [4,6-8]. Moreover, in line with prior research [8], we found evidence that the pandemic led to increased glycaemia, in particular FPG among women. Findings concerning HbA1c seem contradictory, as the exposed group had slightly more favourable changes in HbA1c than the control group, despite the less favourable changes in FPG.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Elevated BP due to the pandemic is in line with prior research on social disruption following natural disasters [4,6-8]. Moreover, in line with prior research [8], we found evidence that the pandemic led to increased glycaemia, in particular FPG among women. Findings concerning HbA1c seem contradictory, as the exposed group had slightly more favourable changes in HbA1c than the control group, despite the less favourable changes in FPG.…”
Section: Discussionsupporting
confidence: 91%
“…In particular, our findings suggest the pandemic negatively affected BP and glycaemia. Elevated BP due to the pandemic is in line with prior research on social disruption following natural disasters [4,[6][7][8]. Moreover, in line with prior research [8], we found evidence that the pandemic led to increased glycaemia, in particular FPG among women.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We performed multiple sensitivity analyses to assess the robustness of our findings. First, we considered an augmented inverse-probability weighting (AIPW) method originally proposed in the missing data literature, which extends the IPW method by adding a regression term as an augmentation [ 48 , 49 , 50 ]. Second, the IPW analysis with the 2017 data only compares the disease risks between the evacuation scenarios as of 2017, and does not assess any earlier point in time.…”
Section: Methodsmentioning
confidence: 99%
“…All countries around the world spend significant financial resources on diagnosing, treating and rehabbing the effects of high blood pressure as one of the most common NCDs (16). Due to the conditions of the disaster-stricken community, trauma and infectious diseases are usually given priority, and non-communicable diseases such as hypertension are usually ignored in the early stages (17).…”
Section: Discussionmentioning
confidence: 99%